Internal Capital Markets and the Competition for Corporate Resources. - Stein, Jeremy C (Journal of Finance, 1997)
This article examines the role of corporate headquarters in allocating scare resources to competing projects in an internal capital market. Unlike a bank, headquarters has control rights that enable it to engage in 'winner-picking'–the practice of actively shifting funds from one project to another. By doing a good job in the winner-picking dimension, headquarters can create value even when it cannot help at all to relax overall firmwide credit constraints. The model implies that internal capital markets may sometimes function more efficiently when headquarters oversees a small and focused set of projects.